Development and validation of a GC-MS method for determination of amphetamine-type stimulants and ketamine in human hair - Tran Viet Hung; Ha Minh Hien; Pham Quoc Chinh; Pham Thi Thu Ha; Nguyen Duc Nhu; Nguyen Duc Tuan (Faculty of Pharmacy, Mahidol University, 2023)
A solid-phase extraction (SPE) followed by gas chromatography-mass spectrometry (GC-MS) method was developed and validated for determination of seven amphetamine-type stimulants (ATSs) including amphetamine (AM), methamphetamine (MA), 3,4-methylenedioxyamphetamine (MDA), 3,4-methylenedioxymethamphetamine (MDMA), 3,4-methylendioxyethylamphetamine (MDEA), para-methoxyamphetamine (PMA), 4-bromo-2,5- dimethoxyamphetamine (DOB), and ketamine (KET), norketamine (NKT) in human hair. Ten milligrams of human hair was washed by water and methanol followed by soaking in a solution of 1% hydrochloric acid in methanol for 18 hours. The analytes from the methanolic extract were isolated by a SPE procedure before being derivatized using heptafluorobutyric anhydride (HFBA) at 80°C for 40 minutes. The selected ion monitoring (SIM) method was used for the quantification of the derivatized compounds. The linear range was from 0.5-40 ng/mg for all of the analytes with the coefficient of determination (R2)>0.9971. The intra-day and inter-day accuracies were in the range of 93.63-112.40% and 94.70-110.20%, respectively. The intra-day and inter-day precision (RSD%) were in the range of 8.72 and 9.73, respectively. Limit of detection (LOD) and limit of quantitation (LOQ) for each analyte were less than 0.10 and 0.32 ng/mg, respectively. The recoveries were in the range of 75.18-89.30%. The GC-MS was used for the hair analysis on 51 subjects suspected to be ATSs and ketamine user. The average content of all the analytes was in the range of 1.14-12.70 ng/mg. On the basis of these results, the method was proved to be effective for identification and quantitation of